Utilization of Research Evidences among Nursing Students-A Multicentred Study in India (International Journal of Nursing Education, 2021)
Background-Nursing services in present era thrives for quality patient care. To maintain the standardof professional practice and best quality care the student nurses need to be updated with recent researchevidences. Evidence Based Practice (EBP) in nursing education is inevitable to keep up the pace with thetechnological advancement and standard nursing practices.Objectives-The present study was designed with the objective to assess the level of utilization of researchevidences among nursing students, to find the association of selected variables with the S-EBPQ scores, tocompare the mean score of S-EBPQ among the different groups of nursing students and to analyse the lowresponse items(score1-2) of SEBPQ.Methodology-The present study is a multi-centred cross-sectional descriptive design conducted amongnursing students(n=276) of selected College of Nursing of India through an online survey. Data collectiontool was a standardised self-administered questionnaire of SEBPQ (Students Evidence Based PracticeQuestionnaire by P Upton, D R Upton & S Evans,2015) consisting of 21 items in four subscales. Statisticalanalysis was done by SPSS-24 software in the form of mean, standard deviation, frequency, percentage andANOVA test.Result-Present study revealed that the total mean score of SEBPQ was 3.89±1.22, practice score was3.35±1.53,attitude score was 4.41±1.78, knowledge/skill score was 3.77±1.35 and communication ofresearch score was 4.06±1.48.The utilization of research evidences were high among 31.52% nursingstudents, moderate among 54.35% and low among 14.13% of nursing students. The negative responseanalysis for all items revealed that the student nurses had lower utilization of evidences related to lack ofcritically appraising the evidences (48.2%), tracking down the evidences (45.28%), integrating the evidenceswith practice (44.6%) and difficulty in formulating clearly answerable research question (41%). There wasa statistically significant association between the S-EBPQ score and the place of residence (p value of0.000018) however there was no association found for the age, education level, marital status, years ofexperience, speciality and designation of nursing students.Conclusion-The study concluded that the nursing students have moderately high utilization of EBP, positiveattitude towards research utilization and communication, however institutional support and revised nursingcurriculum with emphasis on EBP would be necessary to make nursing students more research oriented andupdated.